1993
DOI: 10.1093/nar/21.3.641
|View full text |Cite
|
Sign up to set email alerts
|

The adenovirus DNA binding protein effects the kinetics of DNA replication by a mechanism distinct from NFI or Oct-1

Abstract: Initiation of adenovirus DNA replication in vitro minimally requires the viral TP-DNA template and the precursor terminal protein-DNA polymerase heterodimer (pTP-pol). Optimal initiation occurs in the presence of the cellular transcription factors NFI and Oct-1 and the viral DNA binding protein (DBP). We have studied the influence of these three stimulatory proteins on the kinetics of formation of the pTP-dCMP initiation complex. NFI increases the Vmax of the reaction but does not affect the apparent Km for dC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 62 publications
(54 reference statements)
5
31
0
Order By: Relevance
“…This suggests that a conformational change occurs upon transition from initiation to elongation, most likely after the formation of pTP-CAT. In agreement with this notion, kinetic studies revealed that the K m for dCTP is lower for initiation than for elongation (9). In addition to its synthetic activities, Ad pol also possesses a distributive 3Ј-5Ј-exonuclease activity, shown to be involved in proofreading (10).…”
mentioning
confidence: 60%
“…This suggests that a conformational change occurs upon transition from initiation to elongation, most likely after the formation of pTP-CAT. In agreement with this notion, kinetic studies revealed that the K m for dCTP is lower for initiation than for elongation (9). In addition to its synthetic activities, Ad pol also possesses a distributive 3Ј-5Ј-exonuclease activity, shown to be involved in proofreading (10).…”
mentioning
confidence: 60%
“…At higher dCTP concentrations all pTP⅐CAT products can be extended, indicating that it is an intermediate in replication (1). By using low dCTP concentrations sufficient amounts of the intermediate product accumulate to enable the study of both products in one reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The replication of the linear 36-kilobase pair adenovirus (Ad) 1 DNA initiates at two origins located at either molecular end employing a protein-priming mechanism. Initiation requires at least two viral proteins, the DNA polymerase (pol) and the precursor of the terminal protein (pTP), which acts as the primer and is linked covalently to the first nucleotide, a dCMP molecule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Like the SSBs of these phages, AdDBP cooperatively binds to the displaced DNA strand. However, AdDBP has additional roles during adenovirus DNA replication, like the indirect stimulation of the initiation step by increasing the binding of NFI to the replication origin (48,49), and a direct stimulation by lowering the K m for the first dNTP (50). Taking together these data with the differences displayed by GA-1 SSB with respect to the SSBs of the related phages 29 and Nf, it is possible that GA-1 SSB might be implicated in additional roles to those common to the replication systems of the three phages.…”
Section: Visualization Of the Deletion Mutant Proteins By Electronmentioning
confidence: 99%